Quality of Liquid Organic Fertilizer Combination Gamal Leaves and Tofu Dregs with Banana Stem Bioactivator - Istifarini, Feby; Asngad, Aminah (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2023)
Liquid organic fertilizer is an effective solution to inorganic fertilizers. Gamal leaves and tofu dregs can be used to make fertilizer and banana stem bioactivator to speed up fermentation. The study aim to determine the quality of liquid organic fertilizer (LOF) from the combination of gamal leaves and tofu dregs with the banana stem bioactivators based on sensory properties parameters and N, P, K content. This research method used experimental method with a completely randomized design (CRD). It consists of two factors, As for factor 1, namely the combination of gamal leaves and tofu dregs, P1 = 100 ml : 200 ml, P2 = 120 ml : 180 ml. Factor 2 is banana stem bioactivator, B1 = 100 ml, B2 = 150 ml. Data analysis used descriptive qualitative and quantitative statistics used Two Way ANOVA. In observing the sensory indicators, the average fertilizer yield had a dark brown color, scent like soil, and a pH of 5. Meanwhile, in the content test, only the N content met SNI 19-7030-2004. Thus, it can be concluded that the quality of fertilizer can be used as fertilizer but the color parameters, P and K content do not meet the standards.